Retraction: Down-regulated LncR-MALAT1 suppressed cell proliferation and migration by inactivating autophagy in bladder cancer. Issue 43 (30th September 2022) - Qi, Jiude; Chu, Yanfeng; Zhang, Guangyan; Li, Hongjun; Yang, Dongdong; Wang, Qi
Abstract : Retraction of 'Down-regulated LncR-MALAT1 suppressed cell proliferation and migration by inactivating autophagy in bladder cancer' by Jiude Qi et al., RSC Adv., 2018, 8, 31019–31027, ; https://doi.org/10.1039/C8RA04876B .